Comparative Study of Bioinsecticide Quality of Bintaro Leaf (Cerbera odollam G.) between Laboratory and Pilot Scale - Kurniawan, Indra Saputra; Susinggih Wijana2; Beauty Suestining Diyah Dewanti; Muji Paramuji (Talenta Publisher, 2025)
Bioinsecticide constitutes a sustainable solution to mitigate the deleterious consequences of excessive reliance on synthetic insecticides. Bintaro (Cerbera odollam Gaertn.) is a promising candidate for bioinsecticide production due to its efficacy. However, it is imperative to note that the scale of production significantly impacts the process conditions and the quality of the resulting products. To this end, a comparative study was conducted on the manufacturing of bintaro leaf bio-insecticide on a pilot scale. The objective of this study is to ascertain the discrepancy in saponin content, water content, and toxicity of bintaro extract between laboratory and pilot scale. This study uses the reference of previous research where the best treatment of material to solvent ratio 1:10 (w/v) was obtained, namely using 15 grams of bintaro leaf material and 150 ml of solvent with 7 cycles of socletation. In the pilot scale study there was an increase in the amount of material used to 2 kg of dried bintaro leaves and 30 liters of methanol solvent. The results showed that the crude extract of bintaro leaves had a yield of 27%, saponin content of 0.63%, water content of 19.35%, and toxicity level of 45.33%.